Growth, feed utilization, and body functional composition of snakehead (Channa striatus) fed natural food diets - Bustari Hasan; Indra Suharman; Dian Iriani; Christopher Marlowe A. Caipang (Egyptian Journal of Aquatic Research)
This study aimed to investigate the effect of a 90-day feeding trial of natural food supplements on growth, feed utilization, and body composition in snakehead (Channa striatus). A total of 600 fingerlings (4.07 ± 0.14 g initial weight) were distributed across 12 ponds in 4 triplicate groups. Furthermore, 4 isonitrogenous, isoenergetic diets (45 % crude protein, 18.80 KJ GE g−1) were made by supplementing basal ingredients (fishmeal, salted trash fish, tofu by-product, rice bran) with small fish (SF), field snail (FS), earthworm (EW), or marsh frog (MF). One diet was fed to one triplicate group of the fish at 6 % body weight twice daily. The results showed that EW, FS, and MF groups had higher feed intake than SF, but specific growth rate was consistent among treatments. SF showed lower feed efficiency and lipid retention, with higher protein retention. Body and muscle composition were similar across groups, except for elevated lipid and nitrogen-free extract content in EW group. Muscle albumin, collagen, amino acid, and fatty acid profiles showed no significant difference among dietary treatments, except cysteine which was higher in fish fed with SF diet. Based on these results, SF-supplemented diet was recommended for improved growth, feed utilization, and functional composition in snakehead.